Heat treatment method for improving tensile property of high-temperature titanium alloy used at 700 DEG C
Through multi-step methods of thermal isostatic pressure treatment, solid solution insulation and aging insulation, the structural structure of ZTA35G cast titanium alloy is improved, its tensile performance at 700°C is improved, and the insufficient tissue regulation in the prior art is solved Problem, the tensile strength and elongation after break are significantly improved.
Patent Information
- Application Number
- CN202411566009.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-01-10
AI Technical Summary
The existing ZTA35G cast titanium alloy structure cannot be controlled through thermal deformation, resulting in poor tensile performance at 700°C.
Multi-step heat treatment methods using thermal isostatic pressure treatment, solid solution insulation, air cooling and aging insulation. The specific steps include: heating up the solid solution insulation after hot isostatic pressure treatment, air cooling for the first time, and then heating again for aging insulation and the second Sub-air cooling, adjust the structure of the alloy.
Through this heat treatment method, the tensile strength, yield strength and elongation after break of the alloy are significantly improved, solving the performance optimization problem of ZTA35G cast titanium alloy at 700℃.
Smart Images

Figure CN119287295A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of heat treatment of titanium alloys, and in particular relates to a heat treatment method for improving the tensile properties of a high-temperature titanium alloy used at 700°C. Background Art
[0002] Titanium alloys are widely used in aerospace, energy, chemistry and other fields due to their excellent properties such as high specific strength, heat corrosion resistance, good stability and non-magnetic properties. my country began to study cast titanium alloys for aviation in the late 1950s, and imitated and independently developed TA11, TA12, Ti-60, Ti-600, etc. These cast titanium alloys can meet general needs, but at higher temperatures, such as serving at 700°C, the performance of these alloys is not satisfactory. To this end, ZTA35G alloy was designed by replacing Nd element with Nb element on the basis of Ti60 and increasing the Si element content, in order to improve high temperature creep and high temperature tensile properties. At the same time, the casting method of ZTA35G cast titanium alloy was optimized to reduce the grain size and obtain better performance.
[0003] Metal heat treatment is one of the important links in metal material science and engineering. Through heat treatment, the structure of titanium alloy can be regulated to obtain better mechanical properties. Titanium alloy will undergo phase change during heating and cooling. By controlling the phase change process, different organizational structures can be obtained. Therefore, by controlling the appropriate heat treatment process parameters, the desired microstructure is obtained, thereby improving the mechanical properties and process properties of the alloy. The existing ZTA35G cast titanium alloy has a coarse lamellar structure, which cannot be regulated by thermal deformation, so it is necessary to invent a heat treatment process to improve its mechanical properties. Summary of the invention
[0004] The purpose of the present invention is to provide a heat treatment method for improving the tensile properties of a high-temperature titanium alloy for use at 700°C, thereby solving the problem that the existing ZTA35G cast titanium alloy structure cannot be regulated by thermal deformation.
[0005] The technical solution adopted by the present invention is a heat treatment method for improving the tensile properties of high-temperature titanium alloy for use at 700°C, and the specific steps are as follows: S1. Performing hot isostatic pressing on a ZTA35G cast titanium alloy sample to obtain a first-treated ZTA35G cast titanium alloy; S2, placing the first-treated ZTA35G cast titanium alloy in a heat treatment furnace and continuing to heat it up for solid solution insulation to obtain the second-treated ZTA35G cast titanium alloy; S3, air-cooling the ZTA35G cast titanium alloy after the second treatment to room temperature for the first time to obtain the ZTA35G cast titanium alloy after the third treatment; S4. The ZTA35G cast titanium alloy after the third treatment is placed in the heat treatment furnace again for aging and heat preservation, and finally air-cooled to room temperature for the second time to obtain the ZTA35G cast titanium alloy with improved high-temperature tensile properties.
[0006] The present invention is also characterized in that: The process parameters of hot isostatic pressing are: temperature 1020~1030℃, stress 120~180Mpa, and pressing time 150~200min.
[0007] The temperature during the solution heat preservation process is 1050~1060℃, and the solution heat preservation time is 1~2h.
[0008] During the first air cooling, the cooling rate is 40~70℃ / min until it reaches room temperature. The standing time after reaching room temperature is 30~40min.
[0009] The temperature during the aging and insulation process is 600~700℃, and the aging and insulation time is 3~4h.
[0010] During the second air cooling, the cooling rate is 40~70℃ / min until it drops to room temperature.
[0011] The beneficial effects of the present invention are: The present invention provides a heat treatment method for improving the tensile properties of a high-temperature titanium alloy for use at 700°C. The method comprises the following steps: placing a ZTA35G cast titanium alloy sample after hot isostatic pressing in a heat treatment furnace and heating it to a temperature above the β-phase transformation temperature for solution insulation; then air cooling it to room temperature; placing the sample after the solution treatment in a heat treatment furnace again and heating it to a temperature below the β-phase transformation temperature for aging insulation for a period of time, and then cooling it. Finally, part of the lath α phase of the casting is spheroidized, and fine needle-shaped secondary α phase appears. In addition, more fine and uniform silicides are precipitated at the grain boundaries. Finally, the tensile strength, yield strength, etc. of the alloy heat-treated by the present invention are significantly improved. In addition, the elongation after fracture is also significantly higher than that of the original cast alloy, which solves the problem of how to optimize the performance of ZTA35G through heat treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 It is a schematic diagram of the process of the heat treatment method of ZTA35G casting titanium alloy of the present invention; Figure 2 This is a microstructure photograph of the original cast ZTA35G titanium alloy without heat treatment in Example 1 of the present invention; Figure 3 This is a microstructure photo 1 of the ZTA35G titanium alloy after heat treatment in Embodiment 1 of the present invention; Figure 4 This is a microstructure photo 2 of the ZTA35G titanium alloy after heat treatment in embodiment 1 of the present invention. DETAILED DESCRIPTION
[0013] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0014] Heat treatment methods to improve the tensile properties of high temperature titanium alloys at 700°C, such as Figure 1 As shown, the specific steps are as follows: S1. Performing hot isostatic pressing on a ZTA35G cast titanium alloy sample to obtain a first-treated ZTA35G cast titanium alloy; Among them, the hot isostatic pressing process parameters are: temperature 1020~1030℃, stress 120~180Mpa, and pressing time 150~200min.
[0015] S2, placing the first-treated ZTA35G cast titanium alloy in a heat treatment furnace and continuing to heat it up for solid solution insulation to obtain the second-treated ZTA35G cast titanium alloy; In the process of solid solution insulation, the material is heated to above the β phase transformation temperature (1050~1060℃) for solid solution insulation, and the solid solution insulation time is 1~2h.
[0016] S3, air-cooling the ZTA35G cast titanium alloy after the second treatment to room temperature for the first time to obtain the ZTA35G cast titanium alloy after the third treatment; During the first air cooling, the cooling rate is 40~70℃ / min until it reaches room temperature. The standing time after reaching room temperature is 30~40min.
[0017] S4. The ZTA35G cast titanium alloy after the third treatment is placed in the heat treatment furnace again for aging insulation. During the aging insulation process, it is heated to below the β phase transformation temperature (600-700°C) for aging insulation. The aging insulation time is 3-4 hours. Finally, it is air-cooled to room temperature for the second time. The cooling rate during the second air cooling is 40-70°C / min until it drops to room temperature, so as to obtain the ZTA35G cast titanium alloy with improved high-temperature tensile properties.
[0018] The heat treatment method of the present invention changes the alloy structure as follows: The present invention performs heat treatment on the ZTA35G cast titanium alloy. The initial state of the ZTA35G cast titanium alloy is Widmanstatten structure, with coarse grains, lath thickness between 1-10um, and β phase between lath α phases. After the heat treatment method of the present invention, the alloy structure morphology changes greatly, part of the lath α phase is spheroidized, and fine needle-shaped secondary α phase appears. In addition, the silicide precipitated at the grain boundary is finer and more uniform.
[0019] The principle of improving the high temperature tensile mechanical properties by heat treatment of the present invention is as follows: Solution treatment and aging treatment can reduce the dislocation density and make the crystal structure more uniform, thereby improving the tensile properties of the material. At the same time, the heat treatment of the present invention can spheroidize part of the primary lath α phase, and the spherical α phase can make the grain boundary more continuous and reduce stress concentration. In addition, fine needle-shaped secondary α phase is produced. This structure can increase the number of grain boundaries, thereby effectively hindering the movement of dislocations; and aging will precipitate more fine and uniform silicide precipitation phases, which will also hinder the movement of dislocations. These changes in the organization can improve the tensile properties of the alloy, that is, improve the tensile strength, yield strength, elongation after fracture and cross-sectional shrinkage of the material.
[0020] Example 1 The material used in this embodiment is a ZTA35G titanium alloy cast rod with a diameter of 5 mm and a length of 70 mm, and its composition is Ti-(5.0-6.3)Al-(2.0-5.0)Sn-(2.5-5)Zr-(0.2-1.5).
[0021] Mo-(0.2-2)Nb-(0.2-0.55)Si-(0.2-3)Ta-(0.01-0.09)C, the phase transition point of the alloy is 1026.5℃.
[0022] like Figure 2 The figure shows the microstructure of the original cast ZTA35G titanium alloy without heat treatment. It can be observed from the figure that the ZTA35G alloy presents a coarse Widmanstätten structure in the cast state, and the α phase is clearly visible at the grain boundaries.
[0023] The heat treatment method to improve the tensile properties of high temperature titanium alloy at 700℃ is as follows: S1. Performing hot isostatic pressing on a ZTA35G cast titanium alloy sample to obtain a first-treated ZTA35G cast titanium alloy; Among them, the hot isostatic pressing process parameters are: temperature is 1020°C, stress is 120Mpa, and pressing time is 200min.
[0024] S2, placing the first-treated ZTA35G cast titanium alloy in a heat treatment furnace and continuing to heat it up for solid solution insulation to obtain the second-treated ZTA35G cast titanium alloy; In the process of solid solution insulation, the material is heated to above the β phase transformation temperature (1050°C) for solid solution insulation, and the solid solution insulation time is 1 hour.
[0025] S3, air-cooling the ZTA35G cast titanium alloy after the second treatment to room temperature for the first time to obtain the ZTA35G cast titanium alloy after the third treatment; The cooling rate during the first air cooling is 60°C / min until it reaches room temperature, and the storage time after reaching room temperature is 40 minutes.
[0026] S4. The ZTA35G cast titanium alloy after the third treatment is placed in the heat treatment furnace again for aging insulation. During the aging insulation process, it is heated to below the β phase transformation temperature (700°C) for aging insulation. The aging insulation time is 3 hours. Finally, it is air-cooled to room temperature for the second time. The cooling rate during the second air cooling is 60°C / min until it drops to room temperature, so as to obtain the ZTA35G cast titanium alloy with improved high-temperature tensile properties.
[0027] Table 1 is a comparison of the tensile mechanical properties of the ZTA35G alloy obtained by the heat treatment method of this embodiment and the ZTA35G cast alloy without heat treatment at 700°C. It can be seen from the table that the average tensile strength of the alloy subjected to the heat treatment of the present invention at 700°C is 552Mpa, and the average yield strength at 700°C is 436MPa, which is significantly improved compared with the tensile and yield strength of the original cast state; in addition, the average elongation after fracture at 700°C is 22.17%, which is also significantly higher than that of the original cast alloy.
[0028] Table 1 Tensile mechanical properties of ZTA35G titanium alloy after treatment in Example 1 at 700°C
[0029] Figure 3 , Figure 4 All of them are microstructure photos of ZTA35G titanium alloy after heat treatment in embodiment 1 of the present invention. It can be observed that part of the primary lath α phase is spheroidized. The spherical α phase can make the grain boundary more continuous and reduce stress concentration. In addition, fine needle-shaped secondary α phase is produced. This structure can increase the number of grain boundaries, thereby effectively hindering the movement of dislocations; and aging will precipitate more fine and uniform silicide precipitation phases, which will also hinder the movement of dislocations. These changes in the organization can improve the tensile properties of the alloy, that is, improve the tensile strength, yield strength, elongation after fracture and cross-sectional shrinkage of the material. Example 2 The materials used in this embodiment are the same as those in embodiment 1.
[0030] The heat treatment method to improve the tensile properties of high temperature titanium alloy at 700℃ is as follows: S1. Performing hot isostatic pressing on a ZTA35G cast titanium alloy sample to obtain a first-treated ZTA35G cast titanium alloy; Among them, the hot isostatic pressing process parameters are: temperature is 1030°C, stress is 180Mpa, and pressing time is 150min.
[0031] S2, placing the first-treated ZTA35G cast titanium alloy in a heat treatment furnace and continuing to heat it up for solid solution insulation to obtain the second-treated ZTA35G cast titanium alloy; In the process of solid solution insulation, the material is heated to above the β phase transformation temperature (1060°C) for solid solution insulation, and the solid solution insulation time is 2 hours.
[0032] S3, air-cooling the ZTA35G cast titanium alloy after the second treatment to room temperature for the first time to obtain the ZTA35G cast titanium alloy after the third treatment; The cooling rate during the first air cooling is 40°C / min until it reaches room temperature, and the storage time after reaching room temperature is 30 minutes.
[0033] S4. The ZTA35G cast titanium alloy after the third treatment is placed in the heat treatment furnace again for aging insulation. During the aging insulation process, it is heated to below the β phase transformation temperature (600°C) for aging insulation. The aging insulation time is 4 hours. Finally, it is air-cooled to room temperature for the second time. The cooling rate during the second air cooling is 40°C / min until it drops to room temperature, thereby obtaining the ZTA35G cast titanium alloy with improved high-temperature tensile properties.
[0034] The ZTA35G alloy obtained by the heat treatment method in this embodiment has an average tensile strength of 556 MPa at 700°C and an average yield strength of 440 MPa at 700°C, which are significantly improved compared with the original cast tensile and yield strengths; in addition, its average elongation after fracture at 700°C is 22.51%, which is also significantly higher than the original cast alloy.
[0035] Example 3 The materials used in this embodiment are the same as those in embodiment 1.
[0036] The heat treatment method to improve the tensile properties of high temperature titanium alloy at 700℃ is as follows: S1. Performing hot isostatic pressing on a ZTA35G cast titanium alloy sample to obtain a first-treated ZTA35G cast titanium alloy; Among them, the hot isostatic pressing process parameters are: temperature is 1025°C, stress is 150Mpa, and pressing time is 180min.
[0037] S2, placing the first-treated ZTA35G cast titanium alloy in a heat treatment furnace and continuing to heat it up for solid solution insulation to obtain the second-treated ZTA35G cast titanium alloy; The solid solution heat preservation process is carried out by heating to above the β phase transformation temperature (1055°C), and the solid solution heat preservation time is 1.5h.
[0038] S3, air-cooling the ZTA35G cast titanium alloy after the second treatment to room temperature for the first time to obtain the ZTA35G cast titanium alloy after the third treatment; The cooling rate during the first air cooling is 50°C / min until it reaches room temperature, and the storage time after reaching room temperature is 35 minutes.
[0039] S4. The ZTA35G cast titanium alloy after the third treatment is placed in the heat treatment furnace again for aging insulation. During the aging insulation process, it is heated to below the β phase transformation temperature (650°C) for aging insulation. The aging insulation time is 3.5 hours. Finally, it is air-cooled to room temperature for the second time. The cooling rate during the second air cooling is 50°C / min until it drops to room temperature, so as to obtain the ZTA35G cast titanium alloy with improved high-temperature tensile properties.
[0040] The ZTA35G alloy obtained by the heat treatment method in this embodiment has an average tensile strength of 536 MPa at 700°C and an average yield strength of 420 MPa at 700°C, which are significantly improved compared with the original cast tensile and yield strengths; in addition, its average elongation after fracture at 700°C is 21.21%, which is also significantly higher than the original cast alloy.
Claims
1. A heat treatment method for improving the tensile properties of a high temperature titanium alloy for use at 700°C, characterized in that: The specific steps are as follows: S1. Performing hot isostatic pressing on a ZTA35G cast titanium alloy sample to obtain a first-treated ZTA35G cast titanium alloy; S2, placing the first treated ZTA35G cast titanium alloy in a heat treatment furnace and continuing to increase the temperature for solid solution insulation to obtain the second treated ZTA35G cast titanium alloy; S3, air-cooling the ZTA35G cast titanium alloy after the second treatment to room temperature for the first time to obtain the ZTA35G cast titanium alloy after the third treatment; S4, placing the ZTA35G cast titanium alloy after the third treatment in a heat treatment furnace again for aging and heat preservation, and finally air-cooling to room temperature for a second time to obtain a ZTA35G cast titanium alloy with improved high-temperature tensile properties.
2. The heat treatment method for improving the tensile properties of high temperature titanium alloy for use at 700°C according to claim 1, characterized in that: The hot isostatic pressing process parameters are: temperature of 1020-1030°C, stress of 120-180Mpa, and pressing time of 150-200min.
3. The heat treatment method for improving the tensile properties of high temperature titanium alloy for use at 700°C according to claim 1, characterized in that: The temperature during the solid solution heat preservation process is 1050-1060° C., and the solid solution heat preservation time is 1-2 hours.
4. The heat treatment method for improving the tensile properties of high temperature titanium alloy for use at 700°C according to claim 1, characterized in that: The cooling rate during the first air cooling is 40-70°C / min until the temperature drops to room temperature, and the storage time after dropping to room temperature is 30-40min.
5. The heat treatment method for improving the tensile properties of high temperature titanium alloy for use at 700°C according to claim 1, characterized in that: The temperature during the aging and heat preservation process is 600-700° C., and the aging and heat preservation time is 3-4 hours.
6. The heat treatment method for improving the tensile properties of high temperature titanium alloy for use at 700°C according to claim 1, characterized in that: The cooling rate during the second air cooling is 40-70°C / min until the temperature drops to room temperature.
Citation Information
Cited By
Selective laser melting titanium alloy resistant to high temperature of 700 DEG C and heat treatment process for components of titanium alloy
CN121610724A